Divergent Bird Diversity Patterns Among Four Airports in the Same Bioregion: Assessing Local‐Scale Drivers of Bird Community Assembly - Wan Chen; Caiqian Sun; Yuanyuan Cai; Hang Zhang; Weiya Qian; Peng Li; Xinglong Huang; Qing Chang; Chaochao Hu (Ecology and Evolution)
ABSTRACT The rapid expansion of global aviation has intensified conflicts between aircraft and wildlife, particularly bird strikes, which pose significant safety risks and economic losses. Research on airport bird communities have been extensively conducted at both regional and fine scales; however, studies at the local scale remain relatively limited. This study focuses on four airports in China's Lower Yangtze River Plain. From November 2018 to October 2019, point‐count surveys were conducted across four habitat types (farmland, forest, wetland, and residential areas) at each airport. We recorded 147 bird species across airports, consisting of 50 permanent residents and 96 migrants, with 43 species found to be shared among four airports. Despite shared bioregional characteristics, we found significant variations in bird species richness (H = 61.25, df = 3, p < 0.01), abundance (H = 30.86, df = 3, p < 0.01), and Shannon‐Wiener index (H = 50.49, df = 3, p < 0.01) across the four airports. While Nanjing Lukou International Airport recorded markedly higher species richness (125 species; p < 0.01 based on post hoc tests), the other three airports formed a distinct group with consistently lower diversity levels. This study revealed the impact of seasonal shifts and habitat variations on bird community dynamics, with bird diversity and composition fluctuating significantly between seasons and across different habitat types. Future research should expand the geographic scope of studies and assess the effectiveness of different management strategies in reducing bird strike. Integrating ecological considerations into airport safety protocols is essential for reducing bird strike hazards while conserving local biodiversity.